Modified Tseng's extragradient methods for solving pseudo-monotone variational inequalities. (2nd November 2019) - Thong, Duong Viet; Vuong, Phan Tu
ABSTRACT: We propose two modified Tseng's extragradient methods (also known as Forward–Backward–Forward methods) for solving non-Lipschitzian and pseudo-monotone variational inequalities in real Hilbert spaces. Under mild and standard conditions, we obtain the weak and strong convergence of the proposed methods. Numerical examples for illustrating the behaviour of the proposed methods are also presented